ANALISIS FRAMING PEMBERITAAN LGBT YANG DIKAITKAN HAM DI INDONESIA PADA MEDIA ONLINE DETIK.COM (Periode 1 Januari - 1 Juni 2023) - Arwindra, Bagas Dwi; Sarjono, Herning Suryo; Mahar Rizqi, Fikriana (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The LGBT (lesbian, gay, bisexual, transgender) phenomenon is an issue that is increasingly prevalent in Indonesia, there were at least 119 LGBT organizations in 28 of 34 provinces in 2013. Pros and cons certainly occur in Indonesian society, LGBT is considered to violate existing norms in this country. However, several opinions say that LGBT perpetrators should receive clear human rights protection, the perpetrators also use human rights as a form of their struggle to immediately recognize their existence. LGBT issues related to human rights have also adorned various information media in Indonesia, especially online news portals, including Detik.com, which is the most popular online news portal in Indonesia. Detik.com's framing of this phenomenon is interesting considering that LGBT people have never found clarity regarding their existence and rights. Therefore, this research aims to determine Detik.com's framing regarding LGBT news that is linked to human rights. This research uses qualitative methods and is analyzed using Zhongdang Pan & Gerald M. Kosicki's framing analysis theory with four analytical tools (Syntax, Script, Thematic, Rhetorical). The conclusions from this research also show how Detik.com frames LGBT actors as a group of figures who must have clear rights protection, and recognition of the existence of LGBT is an urgency that needs to be considered so that LGBT actors are no longer subject to acts of discrimination by any party. However, Detik.com also frames LGBT as a group that is at risk and vulnerable in terms of health and a deviation from norms in Indonesia. Keywords: LGBT, human rights, news portal, framing, Zhongdang Pan & Gerald M. Kosicki